2013
DOI: 10.1177/1352458513485146
|View full text |Cite
|
Sign up to set email alerts
|

Wallerian and trans-synaptic degeneration contribute to optic radiation damage in multiple sclerosis: a diffusion tensor MRI study

Abstract: Both trans-synaptic degeneration secondary to optic nerve damage and Wallerian degeneration due to local T2 lesions contribute to OR damage in MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 35 publications
(55 reference statements)
9
44
0
1
Order By: Relevance
“…This supports the scenario put forth by Brown et al where T cells first infiltrate sensory nerves near the meningeal barrier causing trans-synatpic and Wallerian degeneration of cortical neurons leading to microglial activation and secondary inflammation in associated cortex. This is supported by studies in MS patients where optic neuritis and retinal injury were associated with increased levels of MRI abnormality in the optic radiation and visual cortex (Pfueller et al, 2011, Reich et al, 2009, Rocca et al, 2013). …”
Section: Discussionmentioning
confidence: 57%
“…This supports the scenario put forth by Brown et al where T cells first infiltrate sensory nerves near the meningeal barrier causing trans-synatpic and Wallerian degeneration of cortical neurons leading to microglial activation and secondary inflammation in associated cortex. This is supported by studies in MS patients where optic neuritis and retinal injury were associated with increased levels of MRI abnormality in the optic radiation and visual cortex (Pfueller et al, 2011, Reich et al, 2009, Rocca et al, 2013). …”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, patients with relapsing–remitting MS (RRMS) (Pagani et al, 2005) and clinically isolated syndrome (CIS) (Lin et al, 2007) were shown to have abnormal diffusion indices in the corticospinal tract that correlated with lesion load, which was interpreted as being associated with ongoing pathologic processes such as Wallerian degeneration and diffuse inflammation (Ciccarelli et al, 2008). Previous in vivo studies using DTI and tractography in MS patients have demonstrated changes in DTI measures along fibers affected by MS lesions; however, these changes were not associated with the effects of an isolated lesion (Bammer et al, 2000; Rocca et al, 2013; Walsh et al, 2011). In a combined post-mortem histology and MRI study, Kolasinski et al were able to demonstrate diffuse WM damage as a result of a focal MS lesion reflected by DTI measures.…”
Section: Introductionmentioning
confidence: 82%
“…Another study found higher MD values to be correlated with higher T2 lesion volume [118]. These results were consistently interpreted as a consequence of anterograde and retrograde axonal degeneration due to inflammatory lesional impact within the OR [115,118]. One study reported regional RD elevation in the OR parts that were affected by OR-specific white matter lesions corroborating the role of RD as a potential marker for demyelination [91].…”
Section: Optic Radiation Dtimentioning
confidence: 90%
“…Moreover, positive correlations between mean P100 VEP and RD were demonstrated [85], suggesting putative underlying anterograde trans-synaptic degeneration in the visual pathway to occur and to be quantifiable by OR DTI measurements. Whereas one study showed OR FA to be altered in ON patients compared to non-ON patients [115], another study found no changes in all OR DTI indices between the ON and non-ON group, at all [87]. Although OR DTI provides evidence on possible OR damage consecutively following after ON, the concrete processes and mechanisms of trans-synaptic degeneration within the visual system in vivo have still not been fully elucidated.…”
Section: Optic Radiation Dti In Ms-onmentioning
confidence: 97%
See 1 more Smart Citation